MENINGKATKAN KEMAMPUAN KOMUNIKASI DAN KONEKSI MATEMATIK SERTA MINAT BELAJAR SISWA MADRASAH ALIYAH MELALUI PENERAPAN PENDEKATAN PEMBELAJARAN KONTEKSTUAL - Rina Royani; Usuludin Usuludin (Balai Diklat Keagamaan Bandung, 2019)
This paper will present the results of experiments in a class by conducting initial and final tests as well as in the control class by conducting mathematics learning in Madrasah Aliyah through contextual approaches, as an effort to improve communication and mathematical connections and student learning interests. Respondents in this study were 72 students from class X Natural Sciences in the city of Bandung. The instruments used include tests of mathematical communication skills, tests of mathematical connection abilities and questionnaires. Interest in learning mathematics. It was found from the researcher that in the mathematics learning class using a contextual approach, communication skills and mathematical connections were better than ordinary classes, even though both of these abilities were classified as low. While interest in learning mathematics in the experimental class is better than in the control class with moderate differences. As for the other things, it turns out that there is no association between communication abilities and mathematical connections Keywords: Mathematic Communication; Mathematic connection; contextual approach